Effects of management practices on legume productivity in smallholder farming systems in sub-Saharan Africa - Muoni, Tarirai; Jonsson, M.; Duncan, Alan J.; Watson, Christine A.; Bergkvist, Goran; Barnes, Andrew P.; Öborn, Ingrid (Wiley, 2022)
Legumes play a key role in food and nutrition security, providing livestock feed and contributing to soil fertility, in mixed smallholder farms in sub‐Saharan Africa (SSA). The environmental conditions under which smallholder farming is practiced are highly heterogeneous with large differences in management practices among farms resulting in variable legume productivity. A meta‐analysis based on 128 publications was conducted to quantify the effects of intercropping, inoculation with rhizobia, minimum tillage and phosphorus application on legume grain and biomass yield and the amount of biological nitrogen fixation in a range of SSA contexts. To further explain the heterogeneity in the results, legume species, type of inoculant, P‐application rate, altitude, rainfall, soil characteristics and non‐legume companion crops were used as moderators. Intercropping as compared to sole cropping reduced legume biomass and grain yields to varying extents, although the total land equivalent ratio for the sum of the intercrops was higher than 1 (1.2–1.9) in all cases. Expressed as the relative land equivalent ratio (rLER) intercropping affected pigeonpea grain yield the least (rLER 0.9) and faba bean the most (rLER 0.3). The non‐legume companion crops explained some of the heterogeneity where maize and sorghum significantly reduced the legume yields. Inoculation and P application increased legume grain and biomass yield and moderators such as legume species, type of inoculant, soil organic carbon and soil pH further explained the different effects of the management practices on legume productivity. Minimum tillage had no effect on legume productivity, although less data were available than for the other practices. We conclude that intercropping with legumes improves overall productivity and that application of P fertilizer and inoculants increase legume grain and biomass yield. The effect varies with crop species, soil type and other environmental conditions, and this needs to be factored into tailored recommendations supporting decision making in smallholder farming.